If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -125 = 85 + -6c Reorder the terms: -125 + 4x = 85 + -6c Solving -125 + 4x = 85 + -6c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '125' to each side of the equation. -125 + 125 + 4x = 85 + 125 + -6c Combine like terms: -125 + 125 = 0 0 + 4x = 85 + 125 + -6c 4x = 85 + 125 + -6c Combine like terms: 85 + 125 = 210 4x = 210 + -6c Divide each side by '4'. x = 52.5 + -1.5c Simplifying x = 52.5 + -1.5c
| 1+5X=33+7 | | 4x+3(-5x-9)=50 | | 3x+5=5x+5 | | 4x+4x-6=0 | | 107-x=-73-10x | | 7x-2(-x+17)=11 | | 7x+3(-4x-11)=-83 | | 150:2-40=x | | 30=3x(x-3) | | 10=X(X-3) | | -4(-2)=x | | 2+9=19 | | -2x+4x-2=3x-1 | | (5-6i)/(2+3i) | | 2+8=16 | | (2y^2x^0)/4 | | 2y^2x^0/4 | | 3x+19=11x-109 | | .22=8n^2 | | 2x^2+x-351=0 | | x+y=255 | | 59-x=77-7x | | x^3=9x^2 | | 3c+2=-19 | | 9y+18= | | 9y-18=0 | | 2y-3=20 | | 7a-4=30 | | V^2+6v-58=0 | | (2+x)(2+x)(2+x)=1 | | t-3/2=4-3t/4 | | x^2+y^2+z^2-2yz-2zx-2xy=c |